Neurodevelopmental outcomes in preschool children with congenital heart defects: A case-control study using Ages & Stages Questionnaire - Simone Hansen; Cathrine Vedel; Jesper Steensberg; Gorm Greisen; Line Rode; Charlotte Kvist Ekelund; Niels Vejlstrup; Karin Sundberg; Olav Bjørn Petersen; Ditte S. Jørgensen (PLoS ONE, 2026)
Objectives To investigate neurodevelopmental outcome in preschool children with a CHD (congenital heart defect) requiring surgery compared to healthy controls. Materials and methods This study includes all Danish children born between 2016–2018 who underwent surgery within the first year for Ventricular Septal Defect (VSD), atrioventricular septal defect, coarctation of the aorta, double outlet right ventricle, tetralogy of fallot, and Transposition of the Great Arteries (TGA). Exclusion criteria: preterm birth (<37 weeks), twins, and genetic aberrations. Cases were matched with two to four healthy controls on age, sex, gestational age at delivery, and region of birth. Neurodevelopmental outcome at 33–60-months was assessed by the Ages & Stages Questionnaire (ASQ). Comparisons were performed by the Mann-Whitney U test and logistic regression analysis and presented as p -values and odds ratios (OR) with 95% confidence intervals (CI). Results There were no differences in ASQ score between 105 cases with any CHD (230 (IQR 195–260)) and 179 controls (235 (IQR 205–265)), p = 0.12. Cases had five-fold increased odds of a low score compared to controls after adjusting for maternal educational level and children’s age at ASQ completion (OR 5.02, 95% CI 1.49;16.90). This was primarily driven by cases with prenatally undetected VSD, where 20% scored below −2 standard deviations. No differences were found across individual CHD subgroups. In cases with prenatally undetected TGA, the total ASQ score was 185 (IQR 145–190) compared to 220 (IQR 190–270) in prenatally detected TGA, p = 0.08. Conclusions The overall ASQ score in children with surgically corrected CHD was comparable to controls. However, cases had five-fold increased odds of a low score, primarily driven by children with prenatally undetected VSD. Additionally, ASQ scores were lower in TGA cases, especially when undetected prenatally, though not significant. These findings suggest follow-up of all children with a CHD requiring surgery including awareness of potential developmental delays.